2019
DOI: 10.1136/sextrans-2018-053825
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous clearance of urogenital, anorectal and oropharyngealChlamydia trachomatisandNeisseria gonorrhoeaein women, MSM and heterosexual men visiting the STI clinic: a prospective cohort study

Abstract: ObjectiveChlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections can clear without treatment. Despite high prevalence of anorectal infections in men who have sex with men (MSM) and women, studies on anorectal clearance are scarce. Moreover it is unknown whether bacterial load affects urogenital/anorectal CT clearance. In this prospective cohort study, CT and NG clearance is assessed at three anatomical sites of men and women.MethodsCT-positive and NG-positive MSM, heterosexual men and women ≥18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 28 publications
2
41
3
Order By: Relevance
“…Asymptomatic STI are common in pharyngeal and rectal infections. Oro-penile and oro-anal sex as well as the use of saliva are relevant for the transmission of STI, particularly for gonorrhoeae [66,67]. Spontaneous clearance of CT and NG has been reported [67] but sexual abstinence for a not defined time is not an option for most clients.…”
Section: Clinical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic STI are common in pharyngeal and rectal infections. Oro-penile and oro-anal sex as well as the use of saliva are relevant for the transmission of STI, particularly for gonorrhoeae [66,67]. Spontaneous clearance of CT and NG has been reported [67] but sexual abstinence for a not defined time is not an option for most clients.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Oro-penile and oro-anal sex as well as the use of saliva are relevant for the transmission of STI, particularly for gonorrhoeae [66,67]. Spontaneous clearance of CT and NG has been reported [67] but sexual abstinence for a not defined time is not an option for most clients. Even though they can be self-limiting, ECDC and WHO recommend treatment of all asymptomatic pharyngeal NG infections due to their high potential of generating AMR in this localisation through genetic exchange with commensal pathogens.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…In contrast, spontaneous clearance is also seen as with other STIs, e.g. chlamydia and gonorrhoea [33–37]. In a cohort study of Ugandan female sex workers, 55 % of women spontaneously cleared infection within 3 months, 83 % in 6 months and 93 % in 12 months.…”
Section: Natural Historymentioning
confidence: 99%
“…CT disproportionally affects women in terms of its occurrence and burden of sequelae, including pelvic inflammatory disease, ectopic pregnancy, tubal infertility and chronic abdominal pain 3–5. However, spontaneous clearance of urogenital CT has been reported,6 between 19%–54% within 1 year7 8 and 6%–44% between diagnosis and treatment,9–13 using quantitative PCR tests (or nucleic acid amplification tests (NAATs)). Studies on rectal clearance are scarce, reporting 18.2% in men and women (2/11; median interval 11 days)14 and 4.0% (1/25) in men and 18.4% (7/38) in women (median interval 8 days) 13.…”
Section: Introductionmentioning
confidence: 99%
“…However, spontaneous clearance of urogenital CT has been reported,6 between 19%–54% within 1 year7 8 and 6%–44% between diagnosis and treatment,9–13 using quantitative PCR tests (or nucleic acid amplification tests (NAATs)). Studies on rectal clearance are scarce, reporting 18.2% in men and women (2/11; median interval 11 days)14 and 4.0% (1/25) in men and 18.4% (7/38) in women (median interval 8 days) 13. Research demonstrated lower CT bacterial load as the only determinant for clearance 13…”
Section: Introductionmentioning
confidence: 99%